A qualitative investigation of Australian psychologists' perceptions about complementary and alternative medicine for use in clinical practice. (November 2017) - Hamilton, Kyra; Marietti, Vanina
Abstract: This study explored psychologists' knowledge of, attitude toward, and experience with complementary and alternative medicine (CAM) use for clinical purposes. Using a qualitative design, 18 Australian psychologists participated in a semi-structured interview. Psychologists had some understanding about CAM; yet, there was a mismatch between their perceived and actual knowledge. While psychologists were, in general, open toward using CAM with clients they were also sceptical. Attitudes did not overly influence psychologists' views about using CAM in practice, rather adhering to the scientist-practitioner model and embracing a client-centred approach affected their beliefs. Different views emerged as guiding psychologists' use of CAM; however, the codes of conduct played a major role in informing psychologists' use in clinical practice. Psychologists appear open to the idea to use some forms of CAM to enhance client care; yet, they experience unique difficulties such as ethical constraints that may prevent their actual use of CAM for clinical purposes. Highlights: Psychologists have a role to play in the use of CAM in clinical practice. Psychologists, in general, are open toward using CAM with clients but are also sceptical. Adhering to the scientist-practitioner model and client-centred approach affected psychologists' beliefs about CAM use. The codes of conduct played a major role in informing psychologists' use of CAM in clinical practice.